2020
DOI: 10.1177/1078155219901305
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, risk factors and management of cisplatin-induced toxicity: A prospective study

Abstract: Background and propose Cisplatin is a cytotoxic drug that triggers several toxicities. However, nephrotoxicity and ototoxicity remain major clinical limitations. The aim of our study was to evaluate the incidence of chemotherapy toxicity induced by cisplatin and to analyze the influence of risk factors in the Tunisian population. Methods We performed a prospective descriptive study in a period of four months. Patients were eligible if they had pathologically confirmed malignancies and treated with cisplatin-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…In this study, the cisplatin dose selected was enough to produce antitumour efficacy yet still raised concerns regarding bone marrow suppression (Perše and Večerić-Haler 2018 ; Higuchi and Yanagawa 2019 ; Ben Ayed et al. 2020 ; Arita et al. 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the cisplatin dose selected was enough to produce antitumour efficacy yet still raised concerns regarding bone marrow suppression (Perše and Večerić-Haler 2018 ; Higuchi and Yanagawa 2019 ; Ben Ayed et al. 2020 ; Arita et al. 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… 2019 ; Ben Ayed et al. 2020 ). Some of the known mechanisms of organ toxicities of cisplatin are the activation of inflammatory and oxidative stress pathways (Mikuła-Pietrasik et al.…”
Section: Introductionmentioning
confidence: 99%
“…Nephrotoxicity is the most serious adverse effect of cisplatin [ 12 , 13 , 44 , 45 , 46 ], and currently, effective approaches to relieve it are limited. The supplementation with selenium is an interesting topic for alleviating DDP-induced toxicity, but thus far it is still inconclusive [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are approximately 40 specific toxicities of cisplatin, including nephrotoxicity, ototoxicity, hepatotoxicity, cardiotoxicity, gastrointestinal toxicity, neurotoxicity, and hematological toxicity. Among these side effects, nephrotoxicity is the most common one [ 6 , 12 , 13 , 14 , 15 ]. It has been reported that oxidative damage caused by excessive reactive oxygen species (ROS) is one of the main causes of cisplatin nephrotoxicity [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the relative proportions of C-AKI across various equations were not profoundly different for two possible reasons: First, baseline kidney function by eGFR or eCrCl alone has not been consistently shown to predict C-AKI. [36][37][38][39][40][41] Second, our cohort, despite being very large and inclusive, did not have many patients with very low eGFR (ie, patients who would presumably be at highest risk of C-AKI). The mean eGFRCKD-EPI in the <60 ml/min/1.73 m 2 group was 51.3 ml/min/1.73 m 2 .…”
Section: Discussionmentioning
confidence: 99%